Recombinant Acidic Fibroblast Growth Factor Facilitates Motor Recovery and Reduces Myelomalacia in Traumatic American Spinal Injury Association Impairment Scale A Spinal Cord Injured Patients - Wan-Ya Chang; Wen-Cheng Huang; Yun-An Tsai; Lin-Hsue Yang; Yi-Tien Su; Shih-Fong Huang; Chiau-Li Huang; Ya-Hui Lee; Shu-Shong Hsu; Li-Yu Fay (Neurotrauma Reports)
This study aims to evaluate the potential benefits of treating spinal cord injury (SCI) patients with acidic fibroblast growth factor (aFGF), a potent neurotrophic factor that preserves neuronal survival. The study involved 12 tetraplegic patients with American Spinal Injury Association Impairment Scale (AIS) Grade A SCI who were randomly assigned to receive either a recombinant human aFGF or a placebo every 4 weeks for three doses. Participants underwent comprehensive evaluations of medical, neurological, and functional parameters at baseline and every 4 weeks after the first dose until the 48th week. The first dose was administered directly to the injury site during surgery within 6 weeks of the SCI, while the subsequent two doses were administered via lumbar puncture with a 4-week interval. The results revealed promising beneficial effects of aFGF on AIS Grade A SCI patients. The study report highlights aFGF’s potential to expedite motor recovery in complete SCI patients and significantly increase the probability of a 10-point improvement when compared to the placebo group (odds ratio = 6.06, p = 0.0004). Furthermore, aFGF treatment exhibited a significant reduction (p < 0.01) in the incidence or exacerbation rate of myelomalacia, a known secondary complication following SCIs.